Terapia de aceptación y compromiso (ACT) en adultos con trastornos de Ansiedad Social - Calderón Pardo, Oscar Fernando (2023)
Acceptance and Commitment Therapy (ACT) corresponds to a psychotherapeutic intervention system with a contextual approach, developing as an innovative alternative with a research proliferation that aims to demonstrate a solid evidence base for treating different mental health problems. One of them may be social anxiety disorder, characterized by a pattern of recurrent fear and avoidance disturbances during interaction with social situations, affecting the functionality of the individual in different areas of their life. Because this disorder requires strategies and processes that address its treatment appropriately, the idea of understanding the available scientific evidence of this type of therapy in the intervention of this disorder arises. Therefore, the present work aims to describe the scientific evidence and identify the variables that demonstrate the efficacy of ACT in social anxiety disorder in adults and seeks to recognize the prevalent sociodemographic characteristics of the condition. In the methodology, we used a non-experimental design with a qualitative descriptive and cross-sectional approach, in which we developed a bibliographic review, selecting a sample of twelve (N=12) scientific articles. The results indicated that the therapy produced significant changes in the adults who received the treatment, as well as identifying the reported symptom score of social anxiety, psychological flexibility, quality of life, and clinical improvement as the main variables indicating the effect of the therapy. In addition, we found female gender and younger average age to be the prevalent sociodemographic characteristics. In conclusion, ACT has the theoretical properties and empirical foundation to apply to the therapeutic treatment of social anxiety in adults, but it also requires further studies in other contexts